2010
DOI: 10.1002/pro.323
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to efficient production of recombinant angiogenesis inhibitor rhVEGI‐192 and characterization of its structure and antiangiogenic function

Abstract: Methods to prepare pure, bioactive recombinant human vascular endothelial growth inhibitor (rhVEGI), a potent inhibitor of angiogenesis potentially applicable in antiangiogenic cancer therapy, are in urgent demand for preclinical investigation as well as future clinical trials of the protein. Here, we report expression and purification of rhVEGI-192, a recombinant VEGI isoform, comparatively using host strains BL21 (DE3) pLysS and Origami B (DE3) with IPTG-induction and autoinduction techniques. Our study iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Further investigation has shown that the density of the endothelial cells exhibited an 88% decrease within 1 week of treatment with recombinant human VEGI and a further decrease within 3 weeks in Lewis lung cancer murine tumor models. Parr et al reported that patients with breast tumors expressing reduced levels of VEGI had a higher local recurrence, shorter survival time and an overall poorer prognosis than those patients expressing high levels of VEGI (39). Chen et al also reported that purified rhVEGI-192 potently inhibited endothelial growth, induced endothelial apoptosis and suppressed neovascularization in chicken chorioallantoic membrane and demonstrated that VEGI-192 is capable of forming polymeric structure, which is possibly required for its anti-angiogenic activity (40).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation has shown that the density of the endothelial cells exhibited an 88% decrease within 1 week of treatment with recombinant human VEGI and a further decrease within 3 weeks in Lewis lung cancer murine tumor models. Parr et al reported that patients with breast tumors expressing reduced levels of VEGI had a higher local recurrence, shorter survival time and an overall poorer prognosis than those patients expressing high levels of VEGI (39). Chen et al also reported that purified rhVEGI-192 potently inhibited endothelial growth, induced endothelial apoptosis and suppressed neovascularization in chicken chorioallantoic membrane and demonstrated that VEGI-192 is capable of forming polymeric structure, which is possibly required for its anti-angiogenic activity (40).…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described. 64,65 Primary antibodies specific to MMP9, CCND1, STAT3, phospho (p)-STAT3(Tyr705), JAK2, p-JAK2(Tyr1007), GAPDH (1:1,000, Cell Signaling Technology, Danvers, MA, USA), PLAU, Ki-67 (1:1,000, Abcam,), and LRPPRC (1:200, Santa Cruz Biotechnology, Santa Cruz, CA, USA) were used. The blots were then incubated with goat anti-rabbit or anti-mouse secondary antibody (Cell Signaling Technology), and they were visualized using enhanced chemiluminescence.…”
Section: Western Blottingmentioning
confidence: 99%
“…With regard to the evidence that TNF-related apoptosis-inducing ligand and TNFSF14 are also important in PBS/IC (6,8), it may be suggested that TL1A and DR3 elevation is one of the factors contributing to the inflammation and apoptosis in PBS/IC. Secondly, TL1A has been shown to have an anti-angiogenic function (25,26). Upregulation of TL1A and DR3 may inhibit angiogenesis which then causes bladder ischemia and destroys the blood-urine barrier.…”
Section: Discussionmentioning
confidence: 99%